Determinan Struktur Modal Perusahaan Subsektor Konstruksi Bangunan di Bursa Efek Indonesia - Ninin Non Ayu Salmah; Sri Ermeila (Universitas Batanghari Jambi, 2019)
The purpose of this research is to determine the effect of profitabity, asset structure and size on the capital structure of the Building Construction Sub-sector Company in the Indonesia Stock Exchange. This research is quantitative research Population are companies listed on the Building Construction Subsector on the Indonesia Stock Exchange, totaling 16 companies. The observation period is 2014 to 2018. The sample is determined based on non probability sampling with a purposive sampling technique. The total sample is 9 companies. The data used is secondary data. Data collection technique is documentation. Data analysis techniques are multiple linear regression with classical assumption, coefficient of determination and hypothesis test. The results of this research are simultaneously profitability, asset structure and size have a significant effect on capital structure, partially profitability has a negative and not significant effect on capital structure, partially the asset structure and size have positive and significant effect on capital structure, the regression equation is Y = -4,527-0,011X1 + 0.082X2 + 0.414X3 which shows profitability has a negative effect, asset structure and size has a positive effect, the coefficient of determination 34.3% which means the contribution of profitability, asset structure and size to capital structure is 38.8% while the remaining 61.2% is contributed by other variables not analyzed in this research.